Potential economic benefits of the African continental free trade area for Africa and the EU - Julian Hinz; Sonali Chowdhry; Anna Jacobs; Rainer Thiele (Kiel Institute for the World Economy (IfW Kiel), Poverty Reduction, Equity and Growth Network (PEGNet), 2022)
Despite some growth, intra-African trade activity remains at low levels and falls far behind the levels of internal trade observed in more integrated regions like the EU. The European continent remains a major trading partner, but its share in total African exports and imports has decreased from nearly 50% to 35% between 2000 and 2020. Our simulations suggest that implementing the African Continental Free Trade Area (AfCFTA) agreement can lead to substantial welfare gains in Africa, but only if tariff reductions are accompanied by a significant lowering of Non-Tariff-Barriers (NTBs). If NTBs are reduced on a multilateral basis, the EU's declining trade share with Africa might also be reversed. European governments and EU institutions should therefore have an incentive to provide technical and financial assistance - possibly within the framework of the existing WTO-led aid-for-trade initiative - to help AfCFTA economies lowering NTBs on a multilateral basis.
Keywords: 330